Application of project based learning in the discipline of logistics: a case study - Rodrigues, Paulo Cesar Chagas (2011)
Currently the higher education institutions need to search for new tools and methods to make learning more enjoyable and dynamic for students because the job market increasingly needs young people who have the ability to self-criticism above average. A search was performed on a course of action and technologist who had a total of 15 students, for the purpose of this research was to improve the learning level of students, reducing absenteeism and dropout, encourage research and participation in teamwork. As a way to develop this study the students had to develop a project of a bridge made of newspaper and involving the disciplines of logistics, financial management, human resource management and managing projects.